The Kélah Ritual of The Manggaraians in Flores-Eastern Indonesia and Its Theological Significance For Roman Catholics - Alexander Jebadu; Bernardus Raho; Sefrianus Juhani (Center for Research and Development of Religious Literature and Heritage, 2021)
This paper aims to discuss the theological significance of the traditional religious practice of the Manggaraians in Flores, eastern Indonesia called the Kélah Ritual. It is an aspect of the traditional religion of the Manggaraians. The authorities of the Catholic Church in Manggarai have been very tolerant toward the ritual and provide enough space for the Catholics to practice it. The Church, however, does not have a sufficient understanding of its theological significance due to insufficient previous studies on the subject. This paper demonstrates that the ritual has a deep theological significance. This study employed direct observation, direct participation in the Kélah Ritual in several places in Manggarai, focus group discussions, key informant interviews and questionnaires. The results of this research indicate that this ritual is a rite of passage about the human soul departing from this world to heaven conducted a few days or months after the body’s interment. It was on the day of the soul’s ascension to heaven where all of the family ancestors meet with God eternally. This research concludes that, with its theological meaning, the ritual conforms with the Catholic faith doctrine regarding the gradual departure of the human soul to heaven after its corporal death – purgatory. No soul goes right away to heaven when it is not 100% holy. The ritual, therefore, could be valued and officially incorporated into the Catholic faith tradition in order to enrich its worship to God.